Entretien avec Richard Long à propos de White Rock Line (1990, remade 2014) - Richard Long (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Transcript of an interview with Richard Long by art and conservation-restoration students, translated into French. At the occasion of the public presentation, for the French national heritage days, of the restored artwork White Rock Line (1990, remade 2014), the artist met the students, who were able to question him about the work. During the conversation, the artist evokes his points of view on restoration, on art in general and his own work in particular.